Penggunaan Media Video Animasi Berbasis Capcut sebagai Media Dakwah dalam Pembelajaran PAI di Sekolah Dasar - Desi Marliani Rahmania; Anisatul Haq Mustafa; Hana Fitriani; Sariten Handayati; Ani i Nur Aen (Journal on Education, 2023)
This research was conducted based on several problems that occur in elementary schools, one of which is the saturation of students during the learning process. Where students feel bored if learning is only done with the lecture method. Therefore this study aims to see how far the effectiveness of the use of CapCut-based animated video media as a da'wah learning media in PAI learning in elementary schools. The method used in this study is the Design and Development (D&D) method. The research sample consisted of 5th graders at SDN Overtime Situ, with a total of 23 students. The material that we provide is about "Exemplary Prophet Muhammad SAW in Preaching" which has been packaged into the form of an animated video. Based on the results of the study, video-animation-based learning media was considered good by Islamic Religious Education teachers at SDN Lembur Situ with an overall percentage of 78%. It can be concluded that the use of Capcut-based animated video media can increase students' understanding of the Prophet Muhammad's fortitude in preaching. Therefore, it is suggested that CapCut-based animated video media can be used as an effective learning media in teaching PAI in elementary schools.